2022
DOI: 10.1093/jnci/djac163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Development in TP53-Mutated Locally Advanced and Recurrent and/or Metastatic Head and Neck Squamous Cell Carcinoma

Abstract: TP53 mutation is the most frequent genetic event in head and neck squamous cell carcinoma (HNSCC), found in over 80% of patients with HPV-negative disease. As mutations in the TP53 gene are associated with worse outcomes in HNSCC, novel therapeutic approaches are needed for patients with TP53 mutated tumors. The National Cancer Institute (NCI) sponsored a Clinical Trials Planning Meeting (CTPM) to address the issues of identifying and developing clinical trials for patients with TP53 mutations. Subcommittees, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSC) is a common malignant solid tumor that lacks effective treatment options, especially targeted therapies (Mody et al, 2021; Noronha et al, 2022). Although cumulative studies have revealed that human papillomavirus (HPV) infection, mammalian target of rapamycin signaling dysregulation, epidermal growth factor receptor amplification, and TP53 mutation are risk factors for HNSC and participate in tumor development, clinical trials based on these pan‐cancer oncogenic factors have not been very satisfactory (Nathan et al, 2022; Rodriguez et al, 2022; Schinke et al, 2022). Developing efficient therapeutic strategies for HNSC patients based on the concept of precision medicine remains a great challenge (Gu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSC) is a common malignant solid tumor that lacks effective treatment options, especially targeted therapies (Mody et al, 2021; Noronha et al, 2022). Although cumulative studies have revealed that human papillomavirus (HPV) infection, mammalian target of rapamycin signaling dysregulation, epidermal growth factor receptor amplification, and TP53 mutation are risk factors for HNSC and participate in tumor development, clinical trials based on these pan‐cancer oncogenic factors have not been very satisfactory (Nathan et al, 2022; Rodriguez et al, 2022; Schinke et al, 2022). Developing efficient therapeutic strategies for HNSC patients based on the concept of precision medicine remains a great challenge (Gu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%